Excitonic complexes in GaN/(Al, Ga)N quantum dots. (1st February 2017) - Elmaghraoui, D; Triki, M; Jaziri, S; Muñoz-Matutano, G; Leroux, M; Martinez-Pastor, J
Abstract: Here we report a theoretical investigation of excitonic complexes in polar GaN/(Al, Ga)N quantum dots (QDs). A sum rule between the binding energies of charged excitons is used to calculate the biexciton binding energy. The binding energies of excitonic complexes in GaN/AlN are shown to be strongly correlated to the QD size. Due to the large hole localization, the positively charged exciton energy is found to be always blueshifted compared to the exciton one. The negatively charged exciton and the biexciton energy can be blueshifted or redshifted according to the QD size. Increasing the size of GaN/AlN QDs makes the identification of charged excitons difficult, and the use of an Al0.5 Ga0.5 N barrier can be advantageous for clear identification. Our theoretical results for the binding energy of exciton complexes are also confronted with values deduced experimentally for InAs/GaAs QDs, confirming our theoretical prediction for charged excitonic complexes in GaN/(Al, Ga)N QDs. Finally, we realize that the trends of excitonic complexes in QDs are significantly related to competition between the local charge separation (whatever its origin) and the correlation effect. Following our findings, entangled photons pairs can be produced in QDs with careful control of their size in order to obtain zero exciton–biexciton energy separation.